2019
DOI: 10.1111/petr.13632
|View full text |Cite
|
Sign up to set email alerts
|

Growth characterization in a cohort of renal allograft recipients

Abstract: Introduction Growth retardation is a common problem in children with CKD. This study aims to describe growth, prevalence of short stature before RTx, catch‐up growth after RTx, and associated factors. Methods We retrospectively reviewed 74 renal allograft recipients who underwent RTx at Fundación Cardioinfantil, Colombia, between January 2008 and September 2016 with follow‐up for 2 years afterwards. Pre‐RTx Height_SDS and demographic characteristics were compared between children with normal and short stature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…[Zm1]The above clinical characteristics are consistent with previous reports [1,[13][14][15][16][17] . Data from the North American Pediatric Renal Trials and Collaborative Studies (NAPRTCS) annual report [14] reported that the mean Ht-SDS was -1.4 in a cohort of over 1500 patients aged 19 years or more, with 25% of these patients having a Ht-SDS of -2.3 or worse and 10% being below -3.3.…”
Section: Ht-sds At Last Follow-upsupporting
confidence: 88%
See 3 more Smart Citations
“…[Zm1]The above clinical characteristics are consistent with previous reports [1,[13][14][15][16][17] . Data from the North American Pediatric Renal Trials and Collaborative Studies (NAPRTCS) annual report [14] reported that the mean Ht-SDS was -1.4 in a cohort of over 1500 patients aged 19 years or more, with 25% of these patients having a Ht-SDS of -2.3 or worse and 10% being below -3.3.…”
Section: Ht-sds At Last Follow-upsupporting
confidence: 88%
“…In our study 28.8% recipients couldn't met the lower normal limit of height[Zm2] (Ht-SDS <-2), and 64 patients (57.7%) had a height score below -1. Previous other centers reports [15][16]18] showed that the percentage of patients who achieved a normal final height (third centile) ranged from 42 to 75%, as reported in previous studies 62-77% of patients exhibited growth failure at 18 years of age or more.…”
Section: Ht-sds At Last Follow-upsupporting
confidence: 64%
See 2 more Smart Citations